Anomalous increase in specific capacitance in MXene during galvanostatic cycling studies. (September 2022) - Cho, Inho; Selvaraj, Aravindha Raja; Bak, Jinsoo; Kim, Heeje; Prabakar, Kandasamy
Abstract: Layered Ti3 C2 is attracting much attention as a promising electrode material for energy storage devices due to its excellent electrical conductivity and electrochemical properties due to its surface functional groups. Though various methods have been used to etch Ti3 AlC2, the energy storage performance of Ti3 C2 mainly depends on exfoliation of aluminium, surface functional groups and intercalation of potassium. Hence, the optimization of Ti3 AlC2 etching process has been done by hydrothermal, stirring, and ultra-sonication methods which exhibits a different specific capacitance of 8.7 F g −1, 23.75 F g -1, and 141.45 F g −1 respectively in 3 M KOH electrolyte at 2 mA constant current galvanostatic charge/discharge (GCD) analysis even though same etching time and quantity of MAX materials used. Surprisingly, all the samples show an increased specific capacitance up to 2000th cycles and a maximum value of around 170 % is reached and this value is maintained until 5000 charge-discharge cycle at 10 mA by GCD analysis. These electrochemical differences are investigated in terms TiAl bond termination and formation of O-Ti-O bonds due to the removal by Al during etching process. It is found from XPS analysis that -OH surface termination has occurred with F desorption and the interaction of K+ ion has increased the interlayer space between the individual layers. Moreover, the material has been phase transformed from Ti3 C2 to TiO2 /Ti3 C2 hybrid crystal structure during the cycling stability test. The high dipole moment in TiO2 /Ti3 C2 hybrid structure due to the decreased work function has increased the specific capacitance of MXene electrode material. To the best of the authors' knowledge, this has not been observed previously and reported. Highlights: MXene electrode shows abnormal increase in capacitance during galvanostatic cycling. Phase transformed TiO2 /Ti3 C2 hybrid structure shows increased dipole moment. -OH termination, F desorption and K+ intercalation decrease work-function of Ti3 C2 . TiO2 /Ti3 C2 hybrid structure is highly stable.